Nutritional Composition of Seed Kernel and Oil of Wild Edible Plant Species from Western Himalaya, India. Issue 1 (1st January 2021) - Maikhuri, R.K.; Parshwan, Dalbeer S.; Kewlani, Pushpa; Negi, Vikram S.; Rawat, Sandeep; Rawat, L.S.
ABSTRACT: Wild edibles and non-cultivated plants were significantly contributing to nutritional security and livelihood in rural areas of Himalayan region. The rich nutritional value and diversity of secondary metabolites in these plants escaped proper recognition; hence, warranted systematic and research investigation. The present study focuses on the assessment of nutritional composition of three underutilized wild edible fruits i.e. Prinsepia utilis Royle, Prunus persica L. and Neolitsea pallens D.Don. growing wildly in Western Himalaya. The seed kernels of all the selected species were found to be rich sources of nutrients (e.g., lipids, carbohydrates and proteins), minerals (e.g., phosphorus, magnesium, calcium, iron and sodium) and energy value. Edible oil obtained from seed kernels of P. utilis and P. persica were found rich in essential fatty acid (linolenic acid), important unsaturated (omega-6 & omega-9) and saturated fatty acids. Among these, seed kernels of P. utilis possessed maximum quantity of carbohydrate (20.6%) and crude fiber (14.57%), whereas, fat content (70.40%) and energy value (720k cal/100 g) were found maximum for Neolitsea pallens . The results of this study indicated potential of selected species in combating nutritional insecurity.